Uso da ureia em sistema rotacionado de pastagem e seu efeito sobre Rhipicephalus (Boophilus) Microplus (Canestrini: 1887) (Acari: Ixodidae) - Rebeca Passos Bispos Wanderley (2010)
Parasitic infections are recurrent problems in Brazilian herd, which directly affects the agribusiness in the country. This study evaluated the effect of nitrogen fertilization with urea in pastures on the infestation of Rhipicephalus (Boophilus) microplus in twenty lactating crossbred cows, kept on rotational grazing, at the experimental farm of Embrapa Dairy Cattle, Coronel Pacheco, MG. The study was conducted during the period of April 24, 2009 to April 30, 2010, while tick counts were performed on all animals at 14 and 21 days after the tick-bath. The dates of the baths were determined by observing the presence of engorged tick females. Animals were divided in: Treated Group, which were allocated in paddocks fertilized with urea, and Control Group, comprised by animals that grazed the paddocks which received no fertilizer with urea. The results of the scores of individual animals from each group were compared, but there was no significant difference between them (p> 0.05). The second comparison was made based on the analysis of the four groups defined for analysis, group 1, animals in paddocks treated with urea, in the rainy season (T1S1); group 2, animals grazing paddocks not fertilized with urea, during the rainy season (T0S1); group 3, animals allocated in paddocks treated with urea, in the dry season (T1S0), group 4, animals that grazed the paddocks not fertilized with urea, in the dry season (T0S0). There was observed statistical difference (p <0.05) between counts of ticks, groups 1, 2 and 3 were different, and group 4 was equal to Group 1 and 2.